O‘QITUVCHINING PEDAGOGIK FAOLIYATIDA INNOVATSIYALARNING O‘RNI - Pazilova, M.; Haytboyeva, Z. (SCIENCE and SOCIETY, 2018)
The articles reflects the place of innovationis in the work of the teacher. The author of the article states that the higher is the innovation in the educational system , the more efficient is the use of technologies, the broader is the pedagogical outlook.